Analysis of the cycle arrangement of a binary geothermal power plant using a low- and medium-temperature source; Thermal Science and Engineering Progress; Vol. 48 - Alekseenko S. V. Sergey Vladimirovich; Zavorin A. S. Aleksandr Sergeevich; Gubin V. E. Vladimir Evgenievich; Lavrinenko S. V. Sergey Viktorovich; Tsibulskii (Tsibulskiy) S. A. Svyatoslav Anatolievich; Yankovsky S. A. Stanislav Aleksandrovich (2024, 2024)
Title screen